DIALEK BAHASA JAWA NGOKO DESA SITIMULYO KECAMATAN PUCAKWANGI DAN DESA DUKUHMULYO KECAMATAN JAKENAN KABUPATEN PATI - Jumamik Jumamik; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2014)
This study aims to identify the shape ngoko vocabulary and use of particle shape in Javanese dialect Sitimulyo village subdistrict and village Pucakwangi Dukuhmulyo District of Jakenan Pati. This research is descriptive qualitative. The type of this research is descriptive qualitative. Source of data in this research is utterance (oral) which transcribed into writing. The data of this study is the use of the Java language that contain ngoko variations in vocabulary and forms particles that are spoken by indigenous peoples who live in the District Pucakwangi Sitimulyo village and sub-district village Jakenan dukuhmulyo Pati. Methods of data collection in this study was conducted using ably involved refer, recording technique and record engineering. Analysis of the data using the unified method, this method beyond the means of determining the relevant language. Exposure method of data analysis results using informal methods. The results of this study are vocabulary ngoko form and shape of particles using the Java language dialect sentence in the District Pucakwangi Sitimulyo village and sub-district village Jakenan dukuhmulyo Pati. Forms of Javanese dialect vocabulary ngoko Sitimulyo village and sub-district village Pucakwangi dukuhmulyo Jakenan Pati District of experiencing symptoms of phonetic sounds and morphological variation when compared with standard Java language. Variations of the phonetic sounds of symptoms in the form of 1) Change the sound, 2) Removal of phonemes, 3) addition of phonemes. Symptoms include morphological affixation form: prefiksasi, sufiksasi, konfiksasi. The use of particle shape in Javanese dialect Sitimulyo village subdistrict and village Pucakwangi dukuhmulyo Pati District of Jakenan namely: particle softeners, complementary particles, particles priority.